Selective, Stable, Bias‐Free, and Efficient Solar Hydrogen Peroxide Production on Inorganic Layered Materials (Adv. Funct. Mater. 25/2022). (17th June 2022) - Song, Jaejung; Yu, Je Min; Ahn, Jang Hyuk; Cho, Hyeonjin; Oh, Jiyeon; Kim, Yoon Seo; Kim, Jieun; Ko, Myohwa; Lee, Seong‐hun; Shin, Tae Joo; Jeong, Hu Young; Yang, Changduk; et al.
Abstract : Solar Hydrogen Peroxide Production In article number 2110412, Hu Young Jeong, Changduk Yang, Jun Hee Lee, Ji‐Wook Jang, Seungho Cho, and co‐workers report a highly two‐electron oxygen‐reduction pathway‐selective layered double hydroxide catalyst for hydrogen peroxide production. A bias‐free two‐compartment photoelectrochemi cal system with the catalyst can generate hydrogen peroxide with a solar‐to‐hydrogen peroxide conversion efficiency of 3.24%.